2020
DOI: 10.1175/jcli-d-19-0630.1
|View full text |Cite
|
Sign up to set email alerts
|

How Robust is the Asian Precipitation–ENSO Relationship during the Industrial Warming Period (1901–2017)?

Abstract: Instrumental observations (1901–2017) are used to uncover the seasonality, regionality, spatial–temporal coherency, and secular change of the relationship between El Niño–Southern Oscillation (ENSO) and Asian precipitation (AP). We find an abrupt seasonal reversal of the AP–ENSO relationship occurring from October to November in a large area of Asia north of 20°N due to a rapid northward shift of the ENSO-induced subsidence from Indonesia to the Philippines. We identified six subregions that have significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…These teleconnection patterns provide a testbed for understanding the underlying climate dynamics and for assessing climate models' reproducibility of El Niños' climate impacts, which is critical for improved climate predictions. Note that the results shown in Figures 3 and 4 are derived by using the data from 1901 to 2017, and caution should be exercised when applying the results to a shorter period, such as 30–40 years, because the teleconnection pattern may experience multidecadal variations (e.g., Shi & Wang, 2018; Wang et al, 2020; Webster et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These teleconnection patterns provide a testbed for understanding the underlying climate dynamics and for assessing climate models' reproducibility of El Niños' climate impacts, which is critical for improved climate predictions. Note that the results shown in Figures 3 and 4 are derived by using the data from 1901 to 2017, and caution should be exercised when applying the results to a shorter period, such as 30–40 years, because the teleconnection pattern may experience multidecadal variations (e.g., Shi & Wang, 2018; Wang et al, 2020; Webster et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed future changes in precipitation anomalies induced by projected ENSO in East Africa 16 , 19 – 22 , the Maritime continent 23 25 , South and East Asia 17 , 19 , 26 , North America 18 20 , and major monsoon regions 17 , 19 based on enhanced ENSO-teleconnection under anthropogenic forcings. However, a few studies have suggested that the signal for consistent strengthening was relatively weak across the models 17 , 20 , 22 , although the multimodel ensemble mean showed robust increases in ENSO-induced precipitation. A recent study 17 found that in the Coupled Model Intercomparison Project (CMIP) version 6, an El Niño-like eastern Pacific warming reduced North American monsoon rainfall as a result of the equatorward shift of the intertropical convergence zone.…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies have suggested that the signal for consistent strengthening was relatively weak across the models 17 , 20 , 22 , although the multimodel ensemble mean showed robust increases in ENSO-induced precipitation. A recent study 17 found that in the Coupled Model Intercomparison Project (CMIP) version 6, an El Niño-like eastern Pacific warming reduced North American monsoon rainfall as a result of the equatorward shift of the intertropical convergence zone. However, owing to large uncertainties in estimating the changes in SST, future changes in El Niño-induced precipitation in mid-latitude land regions have not been well addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it has been pointed out that ENSO influences the South China Sea (SCS) summer monsoon onset (Zhou and Chan, 2010;Zhu and Li, 2017), the western North Pacific tropical cyclones, and the interannual variation of precipitation (Du et al, 2011;Ge et al, 2016). Negative correlation exists between ENSO and the winter precipitation in Southeast Asia (Wang et al, 2020). However, previous studies about the ENSO influence on Southeast Asia precipitation have mainly concentrated on seasonal averages, while the sub-seasonal characteristics have not yet been comprehensively revealed.…”
Section: Introductionmentioning
confidence: 99%